Percepções de docentes de um curso de medicina frente a alunos com baixo desempenho acadêmico: um estudo qualitativo - Birschner, Laziany Muller (2022)
Entry into Higher Education is something remarkable and its expansion is due to the implementation of public policies that allowed, among other aspects, its democratization. This reality brings a diversity of students with different potentialities and learning rhythms, causing and leveraging countless questions about low academic performance. The medicine course is marked by numberless stressors, which can be negative generators and influence motivation, quality of life, the psychological aspects and, consequently, the student's academic performance. Teachers, in turn, when they perceive disturbances related to students, have doubts about the origin of these problems, which can be behavioral, linked to attitude or some type of anguish, and even a lack of knowledge. Bearing this perspective in mind, the present study tried to describe and analyze the context of medical education for medical students with low academic performance from the perspectives of professors at the José do Rosário Vellano educational institution - UNIFENAS campus BH. With this purpose, the study was presented in the form of a qualitative research, having as instrument of data collection semi-structured individual interviews with 12 professors of the referred institution with the purpose of apprehending the perceptions that professors have in relation to students who present low academic performance. Data collection took place after approval by the Ethics Committee, from September 2021 to December 2021, and data analysis was carried out in sequence using the thematic content analysis technique. The results have pointed to the understanding of students with low academic performance as those who, for the most part, have cognitive difficulties, are unable to make inferences or extrapolations, who have difficulties in applying knowledge in their practical part, in addition to social, psychological and environmental factors being directly related to academic performance. It is concluded that the difficulties presented by the students need to be further explored, which implies involving different actors, such as the teaching institution, professors, students, psychopedagogues, in order to broaden the view of the theme and give the chance of new advances in this field. process still relatively little explored in medical education. In addition, the results of this study may serve to support teacher training on the subject.